Apixaban or enoxaparin: Which is better for thromboprophylaxis after total hip and total knee arthroplasty in Indian patients?. Issue 2 (13th July 2021) - Kunal, Kishor; Banerjee, Sumit; Garg, Pawan Kumar; Elhence, Abhay
Abstract : Both apixaban and enoxaparin are Food and Drug Administration‐approved standard therapy for prophylaxis of deep‐vein thrombosis; however, the superiority of one over the other is still controversial. With an objective to observe efficacy and safety outcomes of apixaban and enoxaparin in patients undergoing total hip (THA) and knee (TKA) arthroplasty, 96 patients undergoing THA/TKA (October 2018 to August 2019) were randomly allocated into 2 groups; ( n = 48) apixaban; and ( n = 48) enoxaparin. Efficacy outcomes and safety outcomes were recorded at 2 and 5 weeks post‐TKA/THA. Follow‐up functional scoring was done at 6 months postoperatively. Apixaban and enoxaparin were found to be equally efficacious in preventing venous thromboembolism; however, apixaban had a better safety profile. The apixaban group had nonsignificant higher tendency for wound discharge, atrial fibrillation and transient ischaemic attack. Enoxaparin had nonsignificant greater tendency for bleeding, wound dehiscence and pulmonary complications. Apixaban is a safe alternative to conventionally used enoxaparin for chemoprophylaxis in patients undergoing THA or TKA.